Gurindam Twelve Raja Ali Haji Reading Training for MTs Hidayatul Ma'arifiyah Students Pangkalan Kerinci Pelalawan Regency - siswanto (JCOMMITS: Journal of Community Empowerment, Inovation, and sustainability, 2024)
This service activity aims to arouse interest in reading Gurindam Dua Belas among MTs Hidayatul Ma'arifiyah students. Apart from that, reading Gurindam can also build students' character and personality because Raja Ali Haji's Gurimdam Dua Belas contains many messages and moral values ​​and Malay culture. The service team conducted a situation analysis with partners and found that students' interest in reading Gurindam Dua Belas was low due to a lack of understanding in reading Gurindam Dua Belas. The method used in this activity is in the form of a lecture because it can increase understanding of literary works, especially Gurindam Dua Belas. Gurindam Twelve can make it more interesting and easy for students to understand and improve students' language and artistic skills.